Evaluation Of Hydroxyapatite From Fish Bone As Potential Protein Adsorber And Filler - Abdullah, Noor Salihah (Universiti Sains Malaysia, 2018)
The main objective of the current work was to demonstrate the fabrication of magnetic hydroxyapatite nanoparticles (MnHA) by the manipulation of electrostatic self-assembly technique between the modified hydroxyapatite and iron oxide nanoparticles (IONPs). Analysis by XRD revealed that calcination is the most suitable method to synthesize HA from fish bone. The application of protein recovery from waste solution was investigated by using Bradford Assay. In the Bradford assay’s analysis, the presence of a distinctive protein concentration has confirmed the attachment of protein from stickwater to the –COOH linkages of HA.The modified HA was characterized by FTIR, SEM and zeta potential analysis. FTIR results showed a noticeable peak at 1414 cm-1 due to the attachment of IONPs on the H surface. The presence of this peak might be contributed by the carboxylic group present on the surface of magnetic HA. Zeta potential analysis revealed a successful attachment of IONPs on HA surface. Therefore, this findings presents the potential application of magnetic HA for protein recovery where the protein attached to the magnetic nanoparticle can be easily separated from the complex mixture by using magnet. To evaluate the properties of HA as filler materials, the morphology of HA samples was characterized using SEM. Instron Tensile Machine were used to identify the physical and mechanical properties obtained. It was found that pure PLA and fish waste blends can provide higher tensile strength compared tothe addition of HA as filler.